Effect of Thickness on Thermal Conductivity Based on Waste Newspaper Particle Board - Theasy, Yoan; Yulianto, Agus; Astuti, Budi (Journal Of Natural Sciences And Mathematics Research, 2017)
Waste newspaper by most people still considered as waste that has not been used optimally, and it is the one of processed materials from wood which has lignocellulose. The material has the potential to produce particle board to test the value of thermal conductivity, which it is expected to be used as heat insulator. The process of producing particle board is by mixing 450 grams pureed newspaper with 260 grams PVAC, then print it with size (12x7)cm2 with the thickness of 0.5cm; 1 cm; 1.5 cm; 2 cm; 2.5 cm; 3 cm. The process to make particle board drying is for 5 days and the test of thermal conductivity using a 100 watt heat source, and an infrared thermometer. The result obtained from the value of thermal conductivity from newspaper particle board is when more higher value of particle board thickness then more higher the thermal conductivity value. From these result it can be concluded that the particle board which can be used as heat insulation material is the one that has a thermal conductivity value of 0.066 W/ mï°C; 0.125 W/ mï°C; 0.0167 W/ mï°C with thickness range of 1 cm to 2 cm.Â©2017 JNSMR UIN Walisongo. All rights reserved.